Catalytic Cathodes: A Highly Reversible Long‐Life Li–CO2 Battery with a RuP2‐Based Catalytic Cathode (Small 29/2019). Issue 29 (19th July 2019) - Guo, Ziyang; Li, Jinli; Qi, Haocheng; Sun, Xuemei; Li, Hongdong; Tamirat, Andebet Gedamu; Liu, Jie; Wang, Yonggang; Wang, Lei
Abstract : In article number1803246, Lei Wang and co‐workers develop a novel catalyst for Li–CO2 batteries. RuP2 nanoparticles (NPs) are highly dispersed on the surface of N, P dual‐doped carbon films (RuP2 ‐NPCF). The Li–CO2 battery with RuP2 ‐NPCF cathode exhibits super‐high capacity, low overpotential, and long cycle performance.